Infection with Saint Louis encephalitis virus in the city of Ribeirao Preto, Brazil: report of one case - Felipe Gonçalves Motta Maia; Juliana Helena Chávez; William Marciel de Souza; Marilia Farignoli Romeiro; Luiza Antunes de Castro-Jorge; Benedito Antônio Lopes da Fonseca; Luiz Tadeu Moraes Figueiredo (International Journal of Infectious Diseases, 2014)
Saint Louis encephalitis virus (SLEV) is a mosquito-borne flavivirus from the Americas. In this report we describe aspects of the laboratory diagnosis of a patient with an acute febrile illness induced by SLEV that was initially diagnosed as dengue by positive IgM-ELISA. Infection with this virus is probably not rare in Brazil, but cases remain undiagnosed. It is necessary to improve the surveillance system, including laboratories, for the diagnosis of SLEV in Brazil.